Trading frequency affects coal mining share returns trading volume and market capitalization - Williyanto, Danang; Nurwati, Solikah; Sarlawa, Rita (JSM: Jurnal Sains Manajemen, 2024)
This study analyses the effect of trading frequency, trading volume, and market capitalization on stock returns in the Coal Mining sector listed on the Indonesia Stock Exchange. The sample in this study amounted to 4 companies selected using the purpose sampling method. The analytical tool used is SPSS version 23. Based on the analysis, the results show that trading frequency significantly affects stock returns. Trading volume has a substantial effect on stock returns. Market capitalization is having a significant impact on stock returns. The magnitude of the influence of the independent variable can affect the dependent variable, which is 45.5%, and the remaining 54.5% is influenced by other factors that are not included in the research model.